Vitality of Tae' Language in Palopo, South Sulawesi - Rusdiansyah Rusdiansyah; Eri Kurniawan; Fidia Ditazam Malik (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study discusses the vitality of the Tae’ language in Palopo city, South Sulawesi. Vitality of Tae’ language can be seen both from its use as a language of daily communication, the number of speakers, documentation, government policies  related  to  the language, and the inclusion of the language in the school curriculum. The method used in this study is a qualitative descriptive method, in  which  interviews  and  observations  were employed. The subjects interviewed were government officials in Palopo city, as well as the people of Palopo. Findings reveal that the vitality of the Tae language in Palopo is vulnerable to extinction. This is characterized by two main indicators: i) very low use of Tae’ language even in the family domain which affects low language transmission as well ;) and the absence of  govermental  policies  in  preserving  and  maintaining  Tae’  language  as  the  identity  of  the Palopo people and the Indonesian.